Development of a Distinct Microbial Community Upon First Season Crop Change in Soils of Long-Term Managed Maize and Rice Fields - Frindte, Katharina; Zoche, Sarah A.; Knief, Claudia (Frontiers in Microbiology, 2020)
The introduction of crop rotation regimes in paddy soils, for example rice in combination with maize, implements the establishment of new paddy fields to compensate for reduced rice production on existing fields. To study responses of the soil and rhizosphere microbiota upon introduction of a new crop species into continuous cropping agroecosystems, we conducted experiments with soils from adjacent fields where rice and maize were grown successively for more than 30 years. In microcosm experiments, rice and maize plants were cultivated in both soils under the respective plant-required management regime, i.e. rice cultivation under flooded conditions and maize under non-flooded conditions. 16S rRNA gene and fungal ITS region amplicon analysis showed that the soil and rhizosphere microbiota was clearly distinct between soils after long-term rice/maize management. Upon change of the management regime, the bulk soil microbiota became different to both, the former microbial community in the soil and the community being characteristic for the respective type of long-term cropping. Nevertheless, the influence of the soil management history remained clearly visible besides the impact of the new management regime. Similar results were observed for the rhizosphere, though the combined effect of plant species and altered management was even more effective in this compartment compared to the bulk soil. The newly introduced crop plant did not take over characteristic members of the rhizosphere microbiota of the previously cultivated crop; instead, some previously rare taxa became enriched. Thus, the formerly grown crop species did not directly affect the recruitment of microorganisms in the rhizosphere of the following crop species. Further, the results show that the rhizosphere and bulk soil microbiota do not develop straight towards the specific microbiota that is characteristic for a continuous cropping system, but reach a distinct stage upon introduction of a new crop species and new management practices.